SUFISTIC THERAPY WITH SPIRITUAL EMOTIONAL FREEDOM TECHNIQUE (SEFT) METHOD FOR HEALING THE BEHAVIOR OF DRUGS ADDICT - Cintami Farmawati (Jurnal Theologia, 2019)
This research is to find out whether Sufistic therapy with the Spiritual Emotional Freedom Technique (SEFT) method can cure the behavior of addicts who seek drugs. Research subjects were 4 (four) drug addicts. The physical dependence on drugs that can be overcome by providing drugs with groups as substances commonly consumed to minimize them, but the hardest thing is to change the behavior of addicts who are looking for drugs and consume them again. This study uses a multiple baseline design with AB follow-up design where A is the baseline, B is a Sufistic therapy with SEFT method which allows the stages of set-up, tune in, and tapping, as well as follow-up. Data analysis in this study uses quantitative analysis and qualitative analysis. The quantitative analysis in this study is in the form of graphical explanations of research, while the qualitative analysis is the result of observations and interviews during the research. The results of this study indicate that the hypothesis is accepted where Sufistic therapy with the SEFT method can cure the behavior of addicts who seek drugs.